Physicochemical and Microstructural Characterization of Injectable Load-Bearing Calcium Phosphate Scaffold - Mazen Alshaaer; Mohammed H. Kailani; Hanan Jafar; Nidaa Ababneh; Abdalla Awidi (Advances in Materials Science and Engineering)
Injectable load-bearing calcium phosphate scaffolds are synthesized using rod-like mannitol grains as porogen. These degradable injectable strong porous scaffolds, prepared by calcium phosphate cement, could represent a valid solution to achieve adequate porosity requirements while providing adequate support in load-bearing applications. The proposed process for preparing porous injectable scaffolds is as quick and versatile as conventional technologies. Using this method, porous CDHA-based calcium phosphate scaffolds with macropores sizes ranging from 70 to 300 μm, micropores ranging from 5 to 30 μm, and 30% open macroporosity were prepared. The setting time of the prepared scaffolds was 15 minutes. Also their compressive strength and e-modulus, 4.9 MPa and 400 MPa, respectively, were comparable with those of the cancellous bone. Finally, the bioactivity of the scaffolds was confirmed by cell growth with cytoplasmic extensions in the scaffolds in culture, demonstrating that the scaffold has a potential for MSC seeding and growth architecture. This combination of an interconnected macroporous structure with pore size suitable for the promotion of cell seeding and proliferation, plus adequate mechanical features, represents a porous scaffold which is a promising candidate for bone tissue engineering.